Marketing Efficiency of Shallot Commodity in Malang Raya - Siswantoro, Ajik; Pariasa, Imaniar Ilmi; Hardana, Andrean Eka; Riyanto, Sugeng; Utomo, Medea Rahmadhani (HABITAT, 2024)
Analyzing the marketing efficiency of shallot commodities is the main objective in this research.The research was located in Malang Raya included Malang City, Batu City, and Malang Regency. The method of taking farming respondents with a simple random sample design was taken based on the parallel formula in 37 people. Selected marketer’s respondent using the snowball sampling method, involving 13 individuals in total. The margin analysis is conducted to analyze the components of marketing costs as well as the share received by each market actors involved in shallot marketing. Profit marketing margin analysis, the ratio of profit was taken over the costs incurred by each marketing institution in the four marketing channels could be said to be generally efficient. The price share that was received by farmers in marketing channel IV is the highest sahre among the other channels. This is a result of farmers selling their shallots to intermediary traders directly. In contrast to marketing channel III, which gives farmers the lowest share. This occurs because of the high selling price difference between retailers and farmers and involves three marketing institutions.